PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Salon Rosna di Desa Gas Alam Badak I Muara Badak) - SAHRUL, MUHAMMAD; DWIJATENAYA, IDA BAGUS MADE AGUNG; Kardinar Wijayanti, Silvana (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2022)
The fierce competition in business environment in acquiring and retaining customers forces business players to adaptively respond to dynamic customersâ€™ needs and wants.Customer satisfaction has always been the key goal of marketers to achieve. Thus, marketing studies try to find out variables affecting customer satisfaction. The purposes of this study was to determine the effect of price perception and service quality simultaneously and partially on customer satisfaction at Rosna Salon in Badak I, Gas Alam Village. Data collected through questionnaire distribution to 65 customers of Rosna Salon based on saturated sampling technique. Then, the data analyzed using multiple linear regression and the result of this study revealed that price perception and service quality have positive and significant effect partially and simultanously on customer satisfaction.Â